Governança binacional em regiões de fronteira inteligentes : um estudo de caso em uma fronteira entre Brasil e Argentina - Palacios, Rosiane Alves (2021)
Smart cities and smart regions are being designed to provide a better quality of life for their citizens. Urban governance appears as a key element to the development and management of cities and regions that aim to become smart. In border regions, which present different dynamics from the other regions of the countries, developing cities and making border regions smart may be possible through the action of subnational governments and the community through the composition of binational governance. The objective was to understand how binational governance works in a border region that seeks to become smart-cross region. It was chosen as a single case study, a border region between Brazil and Argentina with the project La Frontera, a governance classified as binational. This research adopted an exploratory character where the data collection techniques employed were narrative in-depth interviews with actors from the region and members of La Frontera. We also analyzed governance documents that were evaluated by categorizing the data through content analysis using Nvivo software. The results of the research allowed us to understand the dynamics and barriers experienced by the internal and external actors involved in binational governance, issues related to the political and institutional environment with the factors that influence the constitution of binational governance. The reality of the border both motivates and hinders the execution of development actions, but it opens the possibility of integration. Because it has specific characteristics, different from the rest of the country, the border region is not contemplated according to its specificities. The elements of border identity are still not clear for the countries and may not be totally clear for the border citizens themselves. The history of disputes between countries still guides how borders are conceived, how laws are formulated, and how policies are thought out. There are institutions and actors that can bias the focus of governance actions. The existence of organizations that focus on cooperation and integration of border countries does not guarantee that such principles are practiced. Binational governments can assist subnational governments in managing and practicing integration and paradiplomacy and enable the development of smart-cross borders.